Simultaneous measurement of N2, O2, Ar, CO2, CH4, H2 and CO in aqueous and gaseous samples: A detection of N2/Ar shifts in environments - Yoh, M. (Tokyo Univ. of Agriculture and Technology, Fuchu (Japan). Faculty of Agriculture); Takeuchi, M; Toda, H (Japanese Journal of Limnology (Rikusuigaku Zasshi), 1998)
A gas chromatographic system which accurately analyzes major gas constituents in environments is described. The system, which consists of three separation columns and two gas chromatographs equipped with a thermal conductivity detector, is capable of determining N2, O2, Ar, CO2, CH4, H2 and CO simultaneously in both aqueous and gaseous samples. For gaseous samples, a special injection port was devised in the analytical line to eliminate air contamination during sample handling. A test measurement of air-equilibrated water confirmed that the measured concentrations of dissolved gases agreed well with their theoretical values calculated from solubility and atmospheric partial pressures. The preliminary results of groundwater and wetlands samples demonstrate that the entire gas composition in environments could be fully accounted for by the detected gas species. The N2/Ar ratio given by this analysis could be an effective parameter to evaluate both N2 production (denitrification) and N2 consumption (nitrogen fixation) in nature.